Appropriate Curriculum for the 21st Century Lawyer (2010)
For close to five decades, law faculties and the Nigerian Law School teaching has relied on an education model that focuses on theory, providing minimal opportunity for students to learn and apply the practical problem-solving skills critical to becoming a competent lawyer in real world settings. Modern learning theory provides direction, and the tools are available for improving the legal education system to prepare students for the practice of law. The perspectives and recommendations in this article are presented with the intent of encouraging discussion about the future of legal education in Nigeria. This article is broadly divided into five sections i. e. concept analysis, history of legal education, Pre-NUC; the era of NUC; era of Clinical legal cum NUC and finally proposals for developing an ideal curriculum for legal education in Nigeria. The first section provides an overview of the history and status of legal education. The second section discusses the learning theory and how the profession has fared. It provides answers to criticism as it addresses curriculum, teaching, faculty, and affordability. With high optimism for the future of the profession and the legal education system, I invite you to consider and deliberate on the issues raised in this paper. It is not only possible, but essential, to create a Legal Education for the 21st Century. It is remarkable to state that traditionally, lawyers and law teachers have been resistant to change, arguing that the profession is a noble and conservative one thus not allowing fpr any inference whatsoever. The dynamic reality and the challenges of 21st century legal practice require an equally dynamic and timely response. This paper has outlined one such response: i.e. proposing a workable curriculum for training 21st Century lawyers